Queer, trans and intersectional theory in educational practice - Mayo, Cris,Blackburn, Mollie V. (Routledge, 2021)
Offering an examination of educational approaches to promote justice, this volume demonstrates the necessity for keeping race, ethnicity, class, language, and other diversities at the core of pedagogical strategies and theories that address queer, trans, gender nonbinary and related issues.Queer theory, trans theory, and intersectional theory have all sought to describe, create, and foster a sense of complex subjectivity and community, insisting on relationality and complexity as concepts and communities shift and change. Each theory has addressed exclusions from dominant practices and encouraged a sense of connection across struggles. This collection brings these crucial theories together to inform pedagogies across a wide array of contexts of formal education and community-based educational settings. Seeking to push at the edges of how we teach and learn across subjectivities and communities, authors in this volume show that theories inform practice and practice informs theory—but this takes careful attention, reflexivity, and commitment. This scholarly text will be of great interest to graduate and postgraduate students, academics, teachers, libraries and policy makers in the field of Gender and Sexuality in Education, LGBTQ studies, Multicultural Education and Sociology of Education
9781032239255
Keywords: Aufsatzsammlung; bisacsh; Geschlechterforschung; Intersektionalität; Pädagogik; Geschlechtsidentität